Tungkot Tunggal Panaluan is a Symbol of Sangap and Sahala - Ricky Nelson; Marfenas Marolop Sihombing (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to explore the meaning of the use of Tungkot Tunggal Panaluan. The research method used in this research is a qualitative descriptive method which aims to describe systematically, actual and factually using words, sentences and images as supporting data.Data collection techniques in this research are library studies, documentaries and interviews with the source of the heir of Tungkot Tunggal Panaluan.Tungkot Tungkol Panaluan is a stick carved with the faces of seven humans and several animals carved according to actual events from certain wood and have supernatural powers. The research was carried out in Humbang Hasundutan, precisely Huta Gurgur, one of the areas that is one of the origins of the Batak or King clan rest (village). The results of the research are a source of information for understanding the meaning of Tungkot Tunggal Panaluan as a symbol of sahala or sangap.